Kinetic studies of the photocatalytic degradation of Tartrazine - Morales, Graciela del Valle (2012)
Kinetic studies of the photocatalytic degradation of tartrazine are carried out in a batch stirred reactor built in quartz at laboratory scale using TiO2 as catalyst and irradiating the photoreactor with ultraviolet light. An experimental design is performed using as independent variables or factors the catalyst concentration, the calcination temperature of the catalyst and the initial concentration of tartrazine. The obtained kinetic model indicates that the value of the kinetic constant, k, for a first order reaction is high, in the operating conditions studied.This is consistent with the low value of the adsorption constant, K. The experimental data fitted, with the Langmuir-Hinshelwood model, lead to an equation that, in the range of concentrations studied, allows the evaluation of photodegradation and describes well the photoreactivity results.The obtained kinetic model indicates that the value of the kinetic constant, k, for a first order reaction is high, in the operating conditions studied.This is consistent with the low value of the adsorption constant, K. The experimental data fitted, with the Langmuir-Hinshelwood model, lead to an equation that, in the range of concentrations studied, allows the evaluation of photodegradation and describes well the photoreactivity results.